2007
DOI: 10.1038/modpathol.3800727
|View full text |Cite
|
Sign up to set email alerts
|

HDM4 (HDMX) is widely expressed in adult pre-B acute lymphoblastic leukemia and is a potential therapeutic target

Abstract: Human homolog of murine double minute 2 (HDM2) and HDM4 (or HDMX) are negative regulators of p53. HDM4 has not been assessed in precursor B (pre-B) lymphoblastic leukemia (ALL). We examined bone marrow samples obtained at time of diagnosis from 55 adults with pre-B ALL. A tissue microarray composed of 2 cores per specimen was constructed and immunohistochemical techniques were used to assess HDM4, HDM2, p53, and p21. HDM4 was expressed in 39 of 49 (80%) cases. HDM2 was expressed in 14 of 54 (26%). All HDM2-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…In keeping with this hypothesis, it is frequently overexpressed in human cancers that retain wildtype p53 (14)(15)(16)(17)(18). Recent data suggest that even modest variation in Mdm4 levels in mice cause measurable perturbations of p53 tumor suppressive function (19).…”
Section: Introductionmentioning
confidence: 86%
“…In keeping with this hypothesis, it is frequently overexpressed in human cancers that retain wildtype p53 (14)(15)(16)(17)(18). Recent data suggest that even modest variation in Mdm4 levels in mice cause measurable perturbations of p53 tumor suppressive function (19).…”
Section: Introductionmentioning
confidence: 86%
“…This mutation has also been found in five patients with B-lymphoblastic leukemia/lymphoma in our previous studies (four have 119C4G, one has 119C4S). 24 It is located in the Loop-L1 of the central core domain, which contains the sequencespecific DNA-binding activity of the p53 protein (residues 102-292). 34 It is been reported that most p53 mutations occur in this region and result in loss of DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…The RT-PCR reaction products were sequenced and the presence of a HDM4 variant with a short internal deletion of 68 base pairs (bp) was confirmed as shown earlier. 2,24 The expression of both splicing variants, HDM4-S (containing only the p53-binding domain) and HDM4-FL, was increased compared with that of normal CD19 þ B-cells. The HDM4-S to HDM4-FL ratio was significantly increased compared with that of normal CD19 þ B-cells (Po0.02) (Figure 3b).…”
Section: Hdm4 Transcripts Are Aberrantly Overexpressed In Mantle Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Stronger MDMX nuclear than cytoplasmic immunostaining has been found in various tumor histotypes [32][33][34] and, despite its lack of a nuclear signal localization domain (Supplementary Figure 3), 35 it has also been reported that MDMX-S localizes in the nucleus and the cytoplasm. 16 Using an antibody that recognizes only full-length MDMX, stronger nuclear than cytoplasmic labeling was demonstrated by means of IHC in matched FFPE samples of both the WD and the DD components (Figure 3c).…”
Section: Mdmx Protein Expressionmentioning
confidence: 99%